International expansion of locally-owned call center company a strategic prospective through scenario building - Pilarta, Angela Veranga (Technology Management Center, 2011)
It is an established fact that the Philippine call center industry has reached high ground in terms of economic growth, revenues and number of agents working. The call center business offers more opportunities for growth; its maximum potential has not yet been reached due to our cultural mindset. Perhaps it is time for locally owned call centers to evaluate their present business direction and consider the following steps : (1) gradual shift from Business Process Outsourcing (BPO) to Knowledge Process Outsourcing (KPO); and (2) international expansion to increase market territory. Filipinos nurture suppressed ambition and aspiration but generally try to give the best effort at work with a positive attitude. The Philippines is like a magnet for foreign call centers because of the skills and talents of Filipinos-not to mention the ability to speak and understand the English language. Furthermore, there's always a solution at hand from the very creative Filipino, who can also adjust and sacrifice holidays and family occasions for the high demands of the job. It is about time for the Filipinos to expand their horizons, look beyond their shores and export our technological know-how in the call center industry. China beckons as a lucrative target because of its economic boom. This should be a challenge for the Filipinos to maximize their potential especially in the technology sector. The country is blazing the trail in the call center industry and the Filipino people are ready to take on the new challenges and opportunities in this fertile field. Arangkada Philippines, an advocacy paper from the Joint Foreign Chambers of Commerce in the Philippines (JFCCP) recently presented their recommendations on how to promote Philippine competitiveness in global business and noted that over the last five decades Philippines has lagged behind the rest of the ASEAN countries in the area of economic growth in spite of myriad opportunities (see figures 6-8). This special report presents the possible scenarios over the next ten years involving the establishment of a Philippine call center business in China. From the various articles cited, recommendations and web blogs this paper aims to challenge locally owned call centers to form a consortium and embrace the vision of international expansion to China. In "Methodologies," the theoretical frameworks presented are in actual use and practices for more than 5 years in most Foreign Direct Investors (FDI) call centers and have been proven effective in value creation and business sustainability. These will be the foundation upon which the goal of setting up the Philippine call center consortium in China will be built. The Conceptual Framework which is the highlight of this report uses the APEC 10 Steps of Scenario Building Process combined with strategic planning and environmental scanning tools. Since most of the clients who will set up their businesses in China come from the west, SWOT analysis and STEEP analysis are the tools used to evaluate the situation in combination with the Philippine, US and Chinese cultures and business ethics. APEC Ten steps of scenario building process identify the key predictable variables which affect the Philippine call center industry in relation to its expansion to China. This is also used to identify the critical uncertainties in order to prepare for and manage future developments. It should be noted that the three scenarios threshed out and developed in this paper are in line with the improvement of the local call center industry vis-a-vis its goal of establishing a base in China.